Scour and Erosion 2010
DOI: 10.1061/41147(392)40
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Bench for Study of Internal Erosion in Cohesionless Soils

Abstract: Under the internal flow, hydraulic earth structures (dikes, levees, or dams) can incur a migration of particles that can induce a modification of hydraulic and mechanic characteristics. With the objective to characterize this phenomenon named internal erosion and its consequences on mechanical behaviour of granular materials, a large oedopermeameter device is developed. An axial load is applied on specimen and also a downward flow with a constant hydraulic gradient. During the testing time, the bench can measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
2
0
2
Order By: Relevance
“…Three seepage velocities of 0.086 cm/s (52 mm/min), 0.153 cm/s (92 mm/min) and 0.347 cm/s (208 mm/min) were applied to the top of the samples via a perforated top cap filled with glass beads to ensure that the flow was applied as uniformly as possible. Flow velocities and applied hydraulic gradients (Table 2) were comparable with previous studies (Marot et al, 2010;Chang and Zhang, 2012;Ke and Takahashi, 2015).…”
Section: R a F Tsupporting
confidence: 86%
“…Three seepage velocities of 0.086 cm/s (52 mm/min), 0.153 cm/s (92 mm/min) and 0.347 cm/s (208 mm/min) were applied to the top of the samples via a perforated top cap filled with glass beads to ensure that the flow was applied as uniformly as possible. Flow velocities and applied hydraulic gradients (Table 2) were comparable with previous studies (Marot et al, 2010;Chang and Zhang, 2012;Ke and Takahashi, 2015).…”
Section: R a F Tsupporting
confidence: 86%
“…New model might be useful to estimate the settlement and strain of the soil body subjected to internal erosion by following the mass conservation law. The dynamic measurement of soil settlement and strain in the previous studies (Tomlinson and Vaid 2000;Marot et al 2010;Ouyang and Takahashi 2016;Sato and Kuwano 2018;Indiketiya et al 2019) was approximately observed to obey the equation [36]. This is because the deformation of soil body is attributed to the soil loss.…”
Section: Discussion On Application Of Newly Proposed Model In Predicting Erosion From Tests Conducted In Literaturementioning
confidence: 98%
“…The bench (Marot et al, 2010) is composed of an oedo-permeameter cell with a funnel-shaped draining system which is connected to a collecting system. The bench comprises also an axial loading system, a hydraulic control system and a gammadensitometric system.…”
Section: Figure 1 Principle Of the Eodo-permeametermentioning
confidence: 99%